Upaya Meningkatkan Motivasi Belajar Siswa Jalur Kartu Jakarta Pintar (KJP) Melalui Layanan Bimbingan Kelompok Dengan Metode Group Dynamics Pada Siswa Kelas VII-E SMP Negeri 204 Jakarta - Adhiyati, Nurul (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The objective of this research is to improve the learning motivation of students from Kartu Jakarta Pintar (KJP) admission channel by group counseling service on SMPN 204 Jakarta VII-E class students in Academic year 2019/2020 for 10 students. The methods of data collection in this research are learning motivation questionnaire, structured observation, structured interviews, and assessment. The reliability coefficient of the study motivation questionnaire was analyzed using the Product Moment correlation technique, the results were 0.732 which categorized as high.The results showed that the junior high school students from KJP admission channel experienced an improvement as shown by the increase in the average score in each cycle. The average score for pre-action was 106.5, increasing to 148.9 in cycle III. The level of learning motivation in the first cycle is 122.8, the second cycle is 134.0, and the third cycle is 148.9. In addition, the results of interviews, observations and assessments also show improvement in each cycle.